The Impact of Motivation and Work Environment on Organizational Citizenship Behavior with Participatory Leadership Style in Laundry Companies in Pasuruan, Indonesia - Muhammad Sugito; Slamet Harjatno (Indonesian Journal of Law and Economics Review, 2019)
This study aim to determine The Effect of Job Statisfaction, Motivation dan Work Environment on Organizational Citizenship Behavior with participative leadership style as an intervening variable on the Employees of PT. Surabaya Laundry Sentosa. This research is quantitative research with hypothesis testing. The sample used in this study were 60 section / production employees at PT. Surabaya Laundry Sentosa. The analytical tool used in this study is the path analysis technique (path analysis) with the help of software for the operating system called SPSS (Statistical Program for Social Sience) version 25.0. The primary data in this study were obtained from a questionnaire whose measurements used a Likert scale that was tested for validity and reliability. The results of this study prove that job satisfaction influences organizational citizenship behavior (OCB), motivation also influences organizational citizenship behavior (OCB), work environment influences organizational citizenship behavior (OCB), participative leadership style influences organizational citizenship behavior (OCB), In addition, job satisfaction, motivation, work environment and participative leadership style have a direct and indirect influence on organizational citizenship behavior (OCB).